P2-S9.06 Vaginal film microbicides for HIV prevention: a mixed methods study of women's preferences. (10th July 2011) - Fan, M; Ferguson, L; Rohan, L; Meyn, L; Hillier, S
Abstract : Background: Quick-dissolve films hold promise for HIV microbicide formulation with regards to low cost and scalable manufacture. Consideration of women's preferences enhances probable use of promising microbicides. This study examined preferred physical characteristics of quick-dissolve vaginal films for HIV prevention and factors that influenced valuation of HIV prevention. Methods: We conducted a cross-sectional mixed methods study of women aged 18-30 years from two counties in southwestern Pennsylvania to qualitatively and quantitatively assess preferences. During focus groups women handled and evaluated films of varying texture, thickness, size, shape, and appearance. A pre-focus group survey collected demographics, sexual history, and valuation of vaginal product characteristics. A post-focus group survey collected attitudes towards vaginal microbicides. We carried out thematic analysis of focus group transcripts using modified grounded theory. We examined relationships between participant characteristics and valuing HIV prevention using Fisher's exact test. Results: Eighty-four women participated, with a mean age of 23 years and largely white (54%) and black (43%). Only three reported previous use of a vaginal film. Participants preferred films to be smooth and thin (63%), translucent (48%), and 2×2" square size (36%). Translucent and smooth, thin films were perceived as likely to disintegrate rapidly. Smooth, thin films were perceived as more comfortable and less irritating than textured, thick films. Translucent films were thought to represent a balance between discretion and visual discernibility. Easy, accurate insertion, uniform coverage, and adequate HIV prevention efficacy were viewed as advantages of 2"×2" square size films. Engaging in at least one episode of binge drinking in the past year was associated with rating HIV prevention as important (p=0.048). Participants expressed concern regarding sexual intercourse in the context of alcohol intoxication. Factors associated with ranking HIV prevention as the most important characteristic of a vaginal product included higher number of lifetime vaginal sex partners (p=0.001) and black race (p=0.011). Conclusions: Smooth, thin, translucent, and 2"×2" square films were perceived to offer features valued by women in our sample. Women were concerned with issues of use, including insertion, disintegration, and comfort, as well as issues of discretion and efficacy.